Synthesis of Some 1,4-Bis (Substituted 1,3,4-Oxadiazoles and 1,2,4-Triazoles) Benzene From Terephthalic Acid - K. Daoud; E. Mahmood; M. Salih (College of Education for Pure Sciences, 1999)
ABSTRACT In this paper the synthesis of some 1,4-bis-(substituted1,3,4-oxadiazoles and 1,2,4-trizoles) benzene from terephthalic acid is reported. Terephthalic acid was esterified with absolute ethanol in presence of concentrated sulfuric acid to give ethyl terephthalate (1) which was converted to acid hydrazide (2) with hydrazine hydrate in ethanol. The acid hydrazide (2) was treated with phenyl isothiocyanate to give substituted thiosemicarbazide(4), while it's reaction with ammonium thiocyanate gave substituted thiosemicarbazide (3). Treatment of substituted thiosemicarbazide (3) with mercury oxide in methanol gave 1-(5-amino-1,3,4-oxadiazol-2-yl)-4-(2-amino-1,3,4-oxadiazol-5-yl)benzene (5). Compound (5) was treated with hydrazine hydrate in ethanol and with potassium hydroxide in methanol to give substituted 1,2,4-trizole (11) and (7) respectively. 1,2,4-trizolone (9) was synthesized from substituted 1,2,4- triazole (7) with hydrochloric acid. Substituted 1,2,4-triazole (10) was obtained from substituted thiosemicarbazide (4) via 1,3,4-oxadiazole (6) and substituted triazole (8) substituted 1,2,4 triazole (12). The structures of synthesised compounds were confirmed by IR, UV and physical means.